Evaluating Policy Frameworks and Their Role in the Sustainable Growth of Distributed Photovoltaic Generation - Annelys Machado Schetinger; André Frossard Pereira de Lucena (Resources)
In response to the growing photovoltaic distributed generation market, this study investigates the evolution of energy policies and mechanisms driving the growth of photovoltaic distributed generation (DGPV). Analyzing the top ten countries in photovoltaic installations, it examines historical trends in capacity growth, installation costs, and stakeholder engagement to evaluate policy effectiveness. Eight policy categories are identified as follows: direct financial incentives, energy market regulation, government management, production incentives, performance-based feed-in tariffs, renewable energy obligations, research and development initiatives, and agreements and commitments. The research results emphasize the crucial influence of government management policies, direct financial incentives, and energy market regulation on promoting the growth of DGPV. Political will and effective governance are identified as key drivers in advancing technology and market development. Policies reducing installation costs and encouraging investment support the transition of photovoltaic systems from early adoption to market maturity. Despite these advances, disparities in policy implementation highlight the need for adaptable frameworks tailored to local contexts. By leveraging solar energy, an abundant and universally accessible resource, nations can enhance energy equity through effective policies and accelerate the shift toward sustainable energy systems. This analysis offers valuable insights for policymakers seeking to promote DGPV as a central strategy in combating climate change.